A financial road map to scaling up essential child health interventions in 75 countries - Karin Stenberg; Benjamin Johns; Robert W Scherpbier; Tessa Tan-Torres Edejer (The World Health Organization, 2007)
OBJECTIVE: To estimate the additional resources required to scale up interventions to reduce child mortality and morbidity within the context of the fourth Millennium Development Goal's aim to reduce mortality among children aged < 5 years by two-thirds by 2015. METHODS: A costing model was developed to estimate the financial resources needed in 75 countries to scale up priority interventions that address the major causes of mortality among children aged < 5 years, including malnutrition, pneumonia, diarrhoea, malaria and key newborn causes of death such as sepsis. Calculations were made using bottom-up and ingredients-based approaches; this allowed financial costs to be estimated for each intervention, country and year. Costs reflect WHO guidelines on inputs and delivery strategies and encompass the delivery of interventions at community and facility levels. These costs also include programme-specific investments needed at national level and district level. FINDINGS: The scale-up scenario predicts that an additional US$ 52.4 billion will be required for the period 2006-2015. This represents an increase in total per-capita health expenditure in the 75 countries of US$ 0.47 in 2006; this is projected to increase to US$ 1.46 in 2015. Projected costs in 2015 are equivalent to increasing the average total health expenditure from all financial sources in the 75 countries by 8% and raising general government health expenditure by 26% over 2002 levels. (The latest data available at the time of the study were for 2002.) The scale-up scenario indicates that countries with weak health systems may experience difficulties mobilizing enough domestic public funds. CONCLUSIONS: While the results are approximate estimates, they show a substantial investment gap that low- and middle-income countries and their development partners need to bridge to reach the fourth Millennium Development Goal.